Infantile bullous pemphigoid successfully treated with intravenous immunoglobulin therapy. (1st July 2017) - Watanabe, T.; Hara, S.; Muto, J.; Watanabe, D.; Akiyama, M.
Abstract: Click here for the corresponding questions to this CME article.